Find Them Home or Abroad? The Relative Contribution of International Technology In-licensing to "Indigenous Innovation" in China. Issue 3 (June 2015) - Li-Ying, Jason; Wang, Yuandi
Abstract : Innovation policy in China has been promoting "indigenous innovation" by urging Chinese firms to strengthen their internal research and development (R&D) expenditures and to actively acquire external technologies only if they are advanced and necessary. This policy aims to gradually achieve technology excellence and reduce China's reliance on foreign key technologies. But, it is still unclear how international technology in-licensing by Chinese firms, compared with domestic technology in-licensing, has contributed to the indigenous innovation of Chinese firms during the last decade, and whether indigenous innovation policy will continue to make sense in the next decade. This study uses a unique dataset containing information on 178 Chinese firms that were active in technology in-licensing during 2000-2004 — and their patenting activities up to 2009 — to investigate this question. Our findings suggest that, given the importance of R&D, Chinese firms that in-licensed international technologies have performed better with regard to indigenous innovation than those that mainly in-licensed domestic technologies, even though the national innovation policy suggests otherwise. The strategic implications based on the findings for Chinese firms, foreign firms, and policy makers are discussed in detail.